Pengaruh Pengetahuan Pajak, Kebijakan Insentif Pajak dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak - Eka Sari Apriliyanti; David Pangaribuan; Triana Yuniati (Politeknik Kampar, 2024)
The purpose of this study was to test and analyze the effect of tax knowledge, tax incentive policies and fiscal services on taxpayer compliance. This research method uses quantitative research methods, with the type and source of data, namely primary data obtained by distributing questionnaires to individuals in South Tambun. The population and sample of this study were individual taxpayer compliance in South Tambun. The sampling technique used was purposive sampling technique and resulted in 100 samples of processed data that met the criteria. The analysis method used is descriptive statistical test, validity test, reliability test, classical assumption test, multiple linear regression analysis and coefficient of determination analysis, and hypothesis testing. The results of this study indicate that tax knowledge affects taxpayer compliance, tax incentive policies affect taxpayer compliance, taxpayer services affect taxpayer compliance, tax knowledge, tax incentive policies, and taxpayer services simultaneously have a significant effect on taxpayer compliance.